AN INJECTABLE, THERMOSENSITIVE HYDROGEL AS A CELL DELIVERY VEHICLE FOR CARDIAC REGENERATIVE MEDICINE POST-MYOCARDIAL INFARCTION - T. Amirul Muttaqin; Rit Som; Anna Charalambous (Yayasan Adra Karima Hubbi, 2025)
Cell-based therapies for myocardial infarction (MI) are critically limited by poor acute cell retention and viability following direct injection. The harsh, ischemic microenvironment and mechanical washout result in massive cell death, neutralizing therapeutic potential and leading to failed clinical translation. This research aimed to design, synthesize, and evaluate a novel, injectable, thermosensitive hydrogel as a “pro-survival” cell delivery vehicle. The objective was to determine if this biomaterial could solve the critical failure points of retention and viability, thereby enhancing the therapeutic efficacy of mesenchymal stem cells (MSCs) post-MI. A composite hydrogel (Poloxamer/Hyaluronic Acid) was characterized in vitro for its rheological properties (LCST), mechanical stiffness, and cytoprotective capacity under ischemic stress. Its in vivo efficacy was then evaluated in a rat MI model (LAD ligation). The hydrogel+MSCs group (G5) was compared against controls (saline, MSCs-in-saline) via serial echocardiography and post-mortem histomorphometry. In vitro, the hydrogel confirmed ideal thermosensitivity (LCST 37.1°C) and cytoprotection (2.5-fold increase in ischemic cell survival). In vivo, the G5 (hydrogel+MSCs) group demonstrated significantly preserved cardiac function (LVEF 45.2%) compared to the MSCs-only group (G4: 34.1%) at 28 days. This was correlated with significantly reduced infarct size and enhanced border-zone angiogenesis. The thermosensitive hydrogel functions as an essential, enabling technology. It solves the critical failure points of acute retention and viability, demonstrating that an engineered “pro-survival” delivery vehicle is a prerequisite for the successful clinical translation of cardiac cell therapy.